PENGARUH BUDAYA ORGANISASI DAN KEDISIPLINAN KERJA TERHADAP PELAYANAN KESEHATAN DI PUSKESMAS BULAKAMBA BREBES - Medi Tri Purwanto (Jurnal Strategik, 2018)
This study takes the title "The Effect of Organizational Culture and Work Discipline on Health Services in Bulakamba Brebes Health Center". The aim to be achieved in this study was to determine the effect of organizational culture on health services at Bulakamba Health Center in Brebes Regency, to determine the effect of work discipline on health services in Bulakamba Health Center in Brebes Regency, to determine the influence of organizational culture and work discipline on health services at Bulakamba Health Center Brebes Regency and to find out the most influential variables on health services at Bulakamba Health Center in Brebes Regency. Based on the results of the research that has been done, the authors can explain that based on the results of the t-test using a 95 percent confidence level (α / 2 = 0.05 / 2 = 0.025) and the degree of freedom Nk (76-2) obtained t table of 1.994 and the results of the calculation in SPSS shows X1 = 2.809 which means that t count> t table. This shows that Ho is rejected or organizational culture significantly influences health services at Bulakamba Health Center in Brebes Regency. Whereas in X2 it is obtained 2.513 which means that t count> t table. This shows that Ho is rejected or work discipline has a significant effect on health services at Bulakamba Health Center in Brebes Regency. The results of these calculations can be concluded that partially the organizational culture variables and work discipline variables have a significant influence on health service variables in Bulakamba Health Center Brebes District. To find out the regression coefficients as a whole or together, the F Test is used. The F test is carried out using a 95 percent confidence level (α = 0.05) and df = n - k - 1 obtained Ftable of 3.12. While the calculation results show 284,845. This shows that Fcount> Ftable which means Ho's hypothesis is rejected which means that together the independent variables of organizational culture and work discipline influence the health service variables in Bulakamba Health Center in Brebes Regency.